FEMALE AND MALES’ BRAIN TENDENCIES IN LEARNING ENGLISH AS A SECOND LANGUAGE - Naibaho, Lamhot (International Journal of Research -GRANTHAALAYAH, 2020)
This research is about the female and males’ brain tendencies in learning English as a second language, and it was done at Universitas Kristen Indonesia. The purposes of conducting this research is to find out female and males’ brain tendencies in learning English as a second language. This research was a library research, where researchers as "key instruments" of the research that find any information deals with the topic discussed from books, journals and proceedings sourced from “Pubmed, Google Scholar, Research Gate and other online sources” in order to answer the question. The result is that learning English as a second language achievement of students is not influenced by the competence of the right brain or left brain of students, but the left and right brain provides an understanding of the structure and function of the brain. The division of brain function based on the brain hemisphere allows students to gain a deeper understanding of how the brain works to help them improve students' mastery of subjects.